The Effect of Liquidity and Profitability on the Capital Structure as the Moderator Variable of Subsector Retail Companies Listed on Indonesian Stock Exchange - Hantono Hantono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research is to prove and to analyze the effect of liquidity and profitability on the capital structure as the moderator variable of the subsector retail companies listed on Indonesian Stock Exchange in the period of 2011-2015. The population in this research are the listed 16 companies. Using purposive sampling, 10 out of 16 companies are selected as the sample of this research. The data used in this research is secondary data by gathering the necessary information from idx such as the financial report in 2011-2015. The methods that are used in this research to analyze the correlation between the independent variable and dependent variable are multiple regression and assumption testing. In conclusion, it is shown that simultaneously, using f test, independent variables; Cash Turnover and Company Size effect the Return on Assets accordingly with the Debt to Equity Ration as the moderator variable. Partial research result using t test shows that Cash Turnover and Company size effect the Return on Assets partially with Debt of Equity as the moderator variable.